(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
According to him, ‘it is not their fault that we cannot decipher their records.’ Subba Rao (1958 38) was first to use the term ‘Protohistory’, but its usage gained wide currency in the writing of Sankalia (1962). In last few decades, many researchers have been conducted on the early farming communities and it is confirmed from the excavations that the origin of agriculture and animal domestication gave birth to settled life. Therefore, the beginning of settled life, exploitation of natural resources in the surrounding areas started in 9 th -8 th millennium BCE, in various ecological zones like western Asia, China, northwestern part of the Indian subcontinent and middle Ganga plain. The cultures in Indian sub-continent are having regional characteristics with some close affinities with adjoining cultures.